A expansão da educação superior a distância no Tocantins no âmbito da parceria entre a Eadcon e a Unitins - Araújo, Nataniel da Vera-Cruz Gonçalves (Universidade Federal do Rio Grande do Norte, 2017)
This study aims to analyze the expansion of higher education in the form of Distance Education (DE) in the state of Tocantins through partnership between Continuing Education Ltda (EDUCON) and Foundation University of Tocantins (UNITINS) in the period 2000 to 2009. The premise that guides this study is based on the understanding that the relationship established between EADCON and UNITINS for the expansion of higher education in the distance mode is configured as a Public Private Partnership (PPP) according to the principles advocated by the reform of the Brazilian State. The discussion of this theme is the background of the structural changes that capitalist society has been going through in recent years, caused by globalization, productive restructuring and the adoption of the ideals of neoliberalism that guided the reform of the Brazilian state. In this context, knowledge has assumed greater centrality as a condition for countries to enter the globalized world, which has required a higher level of qualification of people, especially with regard to their education at the college level. This view is taken by multilateral agencies like the World Bank, UNESCO, ECLAC which encourage the use of distance education as an expansion strategy for higher education. In this context of strong demands, UNITINS in state public university status, conducts partnership with EDUCON to offer degrees in Tocantins through distance education in the "model" telepresence. As theoretical opted for the historical dialectic materialism as methodological procedures were used, the literature review and documentary analysis of primary and secondary sources. The study concludes that this partnership, the numerical point of view, becomes one of the major policies of expansion of higher education in the country in distance education mode, reaching in 2008 the percentage 33.1% of total income and 28.2% of total enrollment. However, it has its abrupt closure by actions of the Ministry of Education (MEC) and the Federal Public Ministry (MPF) of Tocantins, which found serious irregularities in its operation. Apparently, the partnership was shown as a PPP in recent molds of neoliberal reform, however, studies show that it does not actually constitute a Public Private Partnership on the grounds that disrespects the specific legislation for the establishment of PPPs as Law No. 9.637 / 98, which deals with Social Organizations (OS). Disrespects the Art. 26 of Decree 5,622 / 2005 establishing partnerships that could be made between institutions accredited by MEC and violates Art. 206, item IV of the 1988 Constitution by charging tuition at a public institution. With this, it is found that, in reality, UNITINS / EADCON partnership met the capital interests offering a private educational service using public infrastructure and providing a mass formation, controlled by the market, flexible, lightened and without the quality required under contained in the Technical Note 37/2008 of the Distance Education Department (SEED) of the MEC.